Design of Organic Material Chopping Machine As A Support for Waste Processing Activities at TPST BMR Mandiri (Fakultas Teknik, Universitas Brawijaya, 2025)
TPST BMR “MANDIRI” is a centralized waste disposal site in Bumi Mondoroko Raya Housing. Until now, this TPST only functions as a temporary shelter. The waste that enters this TPST will be sorted into plastic waste and organic waste. Organic waste will be put into a container that will be picked up regularly by the environmental service. One of the main problems of this TPST is the volume of the container. The longer the organic waste that enters the more so that the available containers cannot accommodate it. So a way is needed to overcome this problem. The solution offered is the manufacture of an organic waste chopping machine, especially vegetables. The hope is that with this machine, the volume of containers for organic waste can be reduced and the chopped vegetables can be used for the fertilizer making process. Where the sale of this organic fertilizer can increase the income of this TPST. The output target of this community service activity is the making of a organic material chopping machine with a certain capacity.